Constructing Change or Status Quo. An Analysis of Transitivity Choices in Polish Newspaper Headlines - Anna Łazuka-Banach (Research in Language)
This paper falls into the realm of critical discourse studies by exploring the relationship between particular discourse structures and their meaning as set against a particular socio-political context. To do that it takes the popular analytical tool of transitivity taken from Halliday’s systemic-functional grammar to examine particular configurations of process types as employed by three Polish daily newspapers: Trybuna Ludu [People’s Tribune] - the official voice of the communist authorities, Trybuna [Tribune] - Trybuna Ludu’s ideological successor, and Gazeta Wyborcza [Electoral Newspaper] - the opposition’s newspaper. The time period considered is that between 1944 and 1991, which encompasses a number of defining moments in Polish history, as well as the period of communism and the breakthrough period of political transformation. The analysis mainly looks at process types in headlines featured on the front pages of the three dailies, against a specific historical backdrop and considers their critical potential. As such, the analysis aimed at establishing how particular, dynamic historical/political circumstances were represented through the types of processes in headlines. The results show that the discourse patterns were not only motivated, but also related to social structures in the form of power relations or certain ideological effects. Thus, the analysis is not only revealing when it comes to the notions of agency and control within a specific local context, but also proves the constitutive power of discourse which can both reproduce or change the social world, thus being itself the ‘agent’ of change, but also, and oftentimes instrumental in preserving a status quo.